(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
An ideal biomarker of acute myocardial infarction (AMI) should be sensitive and specific early in the course of the disease and have a high prognostic value, which could help clinicians to choose the most optimal treatment tactics. To date, there is no ideal biomarker of AMI, which would have all the characteristics at the same time.